Project Based Learning Model with 3D Media to Improve Creative Thinking Skill in Elementary Schools - Ikam Sri Zakiatuz; Endang Winarni; Abdul Muktadir; Debi Heryanto; Yusnia Yusnia (Universitas Pendidikan Ganesha, 2026)
The 21st-century education paradigm requires a transformation in learning that shifts focus from mere material mastery to the development of higher-order thinking skills, creativity, and innovation among students. This study employs a quantitative research design known as the Matching Only Pretest-Posttest Control Group Design. Data collection techniques involved administering pretest and posttest assessments. Preliminary analysis included tests for normality and homogeneity. Following these prerequisite tests, hypothesis analysis (inferential) was conducted, including N-Gain tests and correlation tests. The correlation analysis reveals that the sample size (N) is 27, with significant values observed: the significance level (two-tailed) for fluent thinking and flexibility is 0.000, for fluency and originality is also 0.000, and for flexibility and fluency 0.000, as well as for flexibility and originality, which is 0.000. Based on the decision-making criteria derived from these results, it can be concluded that there is a highly significant relationship between flexible thinking and original thinking skills. The implications of this research underscore the importance of implementing teaching models that stimulate and develop creative thinking abilities within educational environments through the use of 3D media. This approach is essential in preparing students to navigate the complexities of a rapidly changing world.